1992
DOI: 10.1105/tpc.4.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of C4 Gene Expression in Developing Amaranth Leaves.

Abstract: lmmunofluorescence microscopy and in situ hybridization were used to examine the expression of genes encoding C4 photosynthetic enzymes during early leaf development in the C4 dicotyledonous grain plant amaranth. During early developmental stages, the chloroplast-encoded large subunit and nuclear-encoded small subunit genes of ribulose-1,8bisphosphate carboxylase/oxygenase (RuBPCase) were expressed in both bundle sheath and mesophyll cells in a C3-type pattern. The RuBPCase proteins and mRNAs became specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
1
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 25 publications
(9 reference statements)
8
84
1
1
Order By: Relevance
“…Using immunofluorescence microscopy and in situ hybridization (Wang et al, 1992), we observed that patterns of RuBPCase gene expression in the apical and basal regions of these leaves were different. In Figures 1A to lD, a series of cross-sections from a typical 7-mm-long leaf were reacted with polyclonal antisera against RuBPCase LSU and SSU, then with R-phycoerythrin-conjugated second antibody.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using immunofluorescence microscopy and in situ hybridization (Wang et al, 1992), we observed that patterns of RuBPCase gene expression in the apical and basal regions of these leaves were different. In Figures 1A to lD, a series of cross-sections from a typical 7-mm-long leaf were reacted with polyclonal antisera against RuBPCase LSU and SSU, then with R-phycoerythrin-conjugated second antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Leaf samples were fixed, embedded in paraffin, sectioned, and reacted with antisera as previously described (Wang et al, 1992). Briefly, primary antiserum against the RuBPCase LSU or SSU was applied to the sections, followed by the application of R-phycoerythrin-conjugated secondary antibody (Sigma).…”
Section: Lmmunolocallzation Analyslsmentioning
confidence: 99%
See 3 more Smart Citations